2007
DOI: 10.1111/j.1365-2559.2006.02555.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of RET/PTC and p53 protein expression in sporadic papillary thyroid carcinoma

Abstract: Our results suggest that immunohistochemistry for both PTC/RET and p53 could be useful in the clinical evaluation of patients with PTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 54 publications
2
32
0
Order By: Relevance
“…The tumor suppressor gene p53 encodes a DNA-binding protein that has important functions in cell cycle arrest, DNA repair, differentiation and apoptosis. p53 gene mutations have been observed in ~50% of the human cancers and are one of the most prevalent types of genetic modifications identified in malignant cells; in addition, these mutations primarily occur in exons (3,4,5,7,8,23). In the thyroid gland, mutations of the p53 gene were reported to occur in 40-62% of undifferentiated carcinomas and 0-25% in well-differentiated carcinomas (4,8).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The tumor suppressor gene p53 encodes a DNA-binding protein that has important functions in cell cycle arrest, DNA repair, differentiation and apoptosis. p53 gene mutations have been observed in ~50% of the human cancers and are one of the most prevalent types of genetic modifications identified in malignant cells; in addition, these mutations primarily occur in exons (3,4,5,7,8,23). In the thyroid gland, mutations of the p53 gene were reported to occur in 40-62% of undifferentiated carcinomas and 0-25% in well-differentiated carcinomas (4,8).…”
Section: Discussionmentioning
confidence: 99%
“…p53 protein overexpression was reported to have an incidence rate of between 11 and 59% (6,22,23). Certain studies regarding the immunohistochemical analysis of p53 protein expression have demonstrated that p53 overexpression may be used as an independent prognostic indicator for differentiated thyroid carcinomas (3)(4)(5)(6)(7)22,24).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations